A scoping review of the economics of multidisciplinary teams in oncology care. (December 2020) - Edney, Laura Catherine; Gray, Jodi; Karnon, Jonathan
Highlights: Multidisciplinary teams (MDTs) are widely used in oncology care. Most economic analyses of MDTs are cost analyses. We found large heterogeneity in study settings, methods and estimated MDT costs. It is unclear if higher costs are associated with better patient outcomes. Cost-effectiveness analyses would inform MDT configurations and patient selection. Abstract: Background: Multidisciplinary Teams (MDTs) are widely used in oncology care, but their cost-effectiveness has not been established. Evidence suggests they are an expensive service to provide and that their effectiveness varies by attendee and patient mix, meeting format, cancer type, stage of disease and specific hospital setting. The aim of this scoping review is to summarise the current literature on resource use and costs of MDTs in oncology care. Methods: PubMed, Embase, Cochrane, and the NHS Economic Evaluation Database (NHS EED) were searched for papers reporting on MDT costs in the treatment of patients with cancer. Results: Database and manual searching identified 2 878 unique potential papers, 2 810 were excluded based on title and abstract screening, and a further 53 were excluded based on full-text review for a final 15 papers for inclusion. Reported costs and resource use required to support an MDT varied considerably across the included studies. No papers reported on the full costs of including MDT discussion as part of patient care and limited detail was provided on MDT configurations and the methodologies employed to calculate costs and resource use. Conclusions: Evidence suggests that specific MDT configurations may likely represent cost-effective care for specific patients in certain contexts, we therefore recommend future investigations into the costs and/or effects of MDTs consider comparisons between different MDT configurations and patient prioritisation processes rather than comparisons between MDT versus no MDT.